Diagnosis, differential diagnosis, and treatment for sudden sensorineural hearing loss: Current otolaryngology practices in China - Chen, Nishan; Karpeta, Niki; Ma, Xin; Ning, Xianhui; Liu, Xiaoling; Song, Jijun; Jiang, Zigang; Ma, Xiulan; Liu, Xiuli; Zhong, Shixun; Sun, Qing; Liu, Jun; et al. (Frontiers in Neurology, 2023)
Introduction Although sudden sensorineural hearing loss (SSNHL) has been attempted to be understood for 70 years, diagnosis and treatment strategies still have strong heterogeneity worldwide, which are reflected in the guidelines issued by countries and the clinical practice of otolaryngologists. Methods Questionnaires were sent to registered otolaryngologists nationwide via an online questionnaire system. We investigated the current views and clinical practices of otolaryngologists in mainland China about the diagnosis, examination, and treatment strategies of SSNHL. Results Most otolaryngologists supported diagnostic classification via audiograms. Regional economic situation and hospital grade affected application strategies for differential diagnosis. Regarding corticosteroid therapy, 54.9% of respondents opted to discontinue the drug 5 days after systemic administration. Both intratympanic therapy and post-auricular injections were selected by more than half of the respondents as initial and salvage treatments. Discussion Chinese otolaryngologists exhibit heterogeneity in clinical practices for SSNHL, including distinct approaches to combination therapy and local application of steroids. This study pointed out Chinese doctors' similarities, differences, and unique strategies in diagnosing and treating SSNHL and analyzed the possible reasons to help the world understand the current otolaryngology practices in China.